Essays in dynamic macroeconomics - Lee, S (2014)
This thesis is concerned with macroeconomic dynamics under various forms of uncertainty. Chapter 2 recognizes that the information flow from the interest rate is impeded when the nominal interest rate hits the zero lower bound. This impediment can (a) increase the duration of zero lower bound episodes and (b) bring about more persistent deflationary pressure. Moreover, it can make the exit from the zero lower bound disorderly. Chapters 3 and 4 are concerned with dynamics of aggregate variables under Knightian Uncertainty. To overcome difficulties with expectations formation under Knightian Uncertainty, the agents follow Interactive Trial and Error Learning (ITEL) (Young, 2009; Pradelski and Young, 2012) to choose investment portfolios. This involves learning by occasionally experimenting with new actions even when the current action proves to be good. Two applications of ITEL are presented. Chapter 3 deals with the growth of aggregate variables.The growth model can match several business cycle features of the US real aggregate wealth data. Chapter 4 considers a portfolio choice problem. The portfolio choice model can match the first two moments of the US real excess return of equity over bonds almost perfectly. Chapter 5 explores “This Time Is Different Syndrome” of Reinhart and Rogoff (2009) in a setting where the agents are learning under Knightian Uncertainty. The agents are grouped into different generations and their models compete in terms of forecasting power. The predecessor’s model is discarded together with the data set when its forecasting power is worse than the current generation’s model. This loss of relevant data is rooted in focusing only on forecasting well in the short-run. By shifting the weight towards finding the true model of the economy, this problem can be substantially reduced.